2019
DOI: 10.1007/s00192-019-03990-1
|View full text |Cite
|
Sign up to set email alerts
|

Long-term mesh erosion rate following abdominal robotic reconstructive pelvic floor surgery: a prospective study and overview of the literature

Abstract: Introduction and hypothesis The use of synthetic mesh in transvaginal pelvic floor surgery has been subject to debate internationally.Although mesh erosion appears to be less associated with an abdominal approach, the long-term outcome has not been studied intensively. This study was set up to determine the long-term mesh erosion rate following abdominal pelvic reconstructive surgery. Methods A prospective, observational cohort study was conducted in a tertiary care setting. All consecutive female patients who… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 87 publications
(56 reference statements)
2
16
1
Order By: Relevance
“…All cases were associated with Ethibond sutures, which created a sinus tract in the vaginal wall. Our findings are in agreement van Zanten et al [27], who reported a mesh erosion rate of 0-13.3% following minimally-invasive SCP. Risk factors for erosion have included total hysterectomy [9,25,28],…”
Section: Discussionsupporting
confidence: 94%
“…All cases were associated with Ethibond sutures, which created a sinus tract in the vaginal wall. Our findings are in agreement van Zanten et al [27], who reported a mesh erosion rate of 0-13.3% following minimally-invasive SCP. Risk factors for erosion have included total hysterectomy [9,25,28],…”
Section: Discussionsupporting
confidence: 94%
“…70 These procedures, however, require both high-technology operating facilities, as well as experienced surgeons, and comes with a median mesh erosion rate of 2-5% . 163,164 In summary, there are many different surgical treatment options in women with a prolapse of the middle compartment. No guidelines currently exist to guide the choice of technique.…”
Section: Study IImentioning
confidence: 99%
“…Our findings are consistent with the estimation by van Zanten et al, who reported an overall median 1.9% mesh reoperation rate following MISC. 12 The overall mesh complication rate after MISC has varied widely in the literature, ranging from 0% to 10.5%, and has been shown prior to be dependent on the type of hysterectomy performed. 6,8,12–14 The seminal Colpopexy and Urinary Reduction (CARE) trial randomized patients to ASC alone or ASC with a Burch colposuspension.…”
Section: Discussionmentioning
confidence: 99%